(untitled) (AYUSHDHARA, 2025)
Hypothyroidism, a prevalent endocrine disorder, leads to metabolic disturbances such as fatigue, weight gain, and reduced metabolism. Ayurvedic formulations, including Thyrovib (Ayurvedaone) and Hamsapadyadi Kashaya (Brihatri), offer promising therapeutic options by targeting the root causes of the disease, such as impaired Agni (digestive fire) and the accumulation of Ama (toxins). Thyrovib, comprising herbs like Brahmi, Gandira (Coleus forskohlii), Kanchanara, Kanchanara guggulu, Punarnava, Trikatu, and Vidanga, synergistically enhances thyroid function, supports metabolism, and promotes detoxification. Similarly, Hamsapadyadi Kashaya, a well-known formulation targets conditions like Galaganda (goitre) and Gandamala (nodular swellings), addressing the pathogenesis of hypothyroidism by stimulating digestion, reducing glandular swelling, and balancing Kapha and Vata doshas. This article discusses how these Ayurvedic remedies, with their unique properties, can complement conventional thyroid treatments by improving hormone synthesis, enhancing metabolic activity, and alleviating common hypothyroid symptoms. Further studies are necessary to validate their clinical efficacy in large populations.